SPICEcore Advection ... - Fudge, T. J. (U.S. Antarctic Program (USAP) Data Center, 2020)
The South Pole Ice Core (SPICEcore), which spans the past 54,300 years, was drilled far from an ice divide such that ice recovered at depth originated upstream of the core site. If the climate is different upstream, the climate history recovered from the core will be a combination of the upstream conditions advected to the core site and temporal changes. Here, we evaluate the impact of ice advection on two fundamental records from SPICEcore: accumulation rate and water isotopes. We determined past locations of ice deposition based on GPS measurements of the modern velocity field spanning 100 km upstream, where ice of ~20 ka age would likely have originated. Beyond 100 km, there are no velocity measurements, but ice likely originates from Titan Dome, an additional 90 km distant. Shallow radar measurements extending 100 km upstream from the core site reveal large (~20%) variations in accumulation but no significant trend. Water isotope ratios, measured at 12.5 km intervals for the first 100 km of the flowline, ...